Religious, Feminist, Activist: Cosmologies of Interconnection - Zwissler, Laurel (Anthropology of contemporary North America, 2018)
Cover; Title Page; Copyright Page; Contents; List of Illustrations; Acknowledgments; Introduction; 1. Changing Rituals, Changing Worlds; 2. â#x80;#x9C;The Shrine Was Human Rightsâ#x80;#x9D;; 3. â#x80;#x9C;Spiritualityâ#x80;#x9D; as Feminist Third Choice; 4. Self, Community, and Social Justice; Conclusion; Source Acknowledgments; Notes; Bibliography; Index